2009
DOI: 10.1210/jc.2008-2045
|View full text |Cite
|
Sign up to set email alerts
|

Fetal and Postnatal Growth and Body Composition at 6 Months of Age

Abstract: Catch-down in weight in the third trimester was strongly associated with postnatal catch-up within 6 wk after birth, and both were associated with an increase in fat mass at the age of 6 months. Our study shows that fetal as well as postnatal growth patterns are associated with body composition in early childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 36 publications
5
52
0
Order By: Relevance
“…Similar results were reported by Ay et al, 30 who found a stronger association of weight gain with FM than with lean body mass at 6 months. Chomtho et al 6 showed in a sample of children who were born healthy at term, that growth during the first 6 months of life was associated more strongly with FM than with fat-free mass during childhood and adolescence.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were reported by Ay et al, 30 who found a stronger association of weight gain with FM than with lean body mass at 6 months. Chomtho et al 6 showed in a sample of children who were born healthy at term, that growth during the first 6 months of life was associated more strongly with FM than with fat-free mass during childhood and adolescence.…”
Section: Discussionsupporting
confidence: 90%
“…Early postnatal catch-up growth has been reported to be a risk factor for insulin resistance (39) or elevated blood pressure (40) in later life. Furthermore, infants with growth faltering in the third trimester have shown more catch-up growth in the first 6 wk of life, which was related to increased fat mass at 6 mo (41). The altered intrauterine growth observed in infants born to FA users may expose them to higher risks for chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements at these visits included physical examinations (height, weight, head circumference, skinfold thickness and waist-hip ratio, Touwen's Neurodevelopmental Examination at the ages of 1.5, 6, 14, and 24 months) and ultrasound examinations (brain structures at 1.5 months and cardiac and kidney structures at the ages of 1.5, 6 and 24 months, abdominal fat at the age of 24 months) [224][225][226][227][228][229][230][231][232][233][234][235][236][237]. Dual 9 Energy Absorptiometry (DXA) scanning was performed in a subgroup of children at the age of 6 months [238]. Similarly Fractional Exhaled Nitric Oxide (FeNO) has been measured in only 50% of all children at the ages of 6 and 24 months.…”
Section: Questionnairesmentioning
confidence: 99%